STUDY OF COOLING TOWER SYSTEM FOR ENERGY EFFICIENCY OPERATION - NAGALINGAM, HARIKRISHNAN (Universiti Teknologi Petronas, 2004)
This study shows how by reducing the cooling water circulation rate, improves the efficiency ofthe operations in the cooling tower system. This is done without modifying the internals of the current cooling towers such as the fills, water treatment programme and air flow rate. This study is applicable for all existing plants with the cooling tower system. This study shows the redistribution ofcooling water in the cooling tower water network. This study with detail calculations are tested for chillers, distillation condensers and air conditioners. The cooling tower performance curve is used as the tool for this analysis. The benefits of this study are colder cooling water temperature, reduce the compression work of the refrigeration cycle by 3.0 % for every 0.6 C reduction inthe cooling water temperature, reduce the cooling tower water consumption, reduce the cooling tower water treatment chemical consumption, reduce the cooling water circulation pump power consumption, and increase the heat transfer of the distillation condensers (increase production).